If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -6 = 6x + 1 Reorder the terms: -6 + 7x = 6x + 1 Reorder the terms: -6 + 7x = 1 + 6x Solving -6 + 7x = 1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6 + 7x + -6x = 1 + 6x + -6x Combine like terms: 7x + -6x = 1x -6 + 1x = 1 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + 1x = 1 + 0 -6 + 1x = 1 Add '6' to each side of the equation. -6 + 6 + 1x = 1 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = 1 + 6 1x = 1 + 6 Combine like terms: 1 + 6 = 7 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| 3x+13=5x-27 | | z^3=13j | | -22+21=m-10 | | H=9x+4c-9+3x-8c+3 | | 9C=72WHATISC | | M=-8x+2z-6+3x-4z+3 | | 23(9+x)=-5(4-x) | | 6+2(16-1*6)= | | SolveT=M(3+FG)forG | | D=-2y+9x-9+4y-9x+6 | | x^2-7x+90=0 | | 1(2x-1)/33 | | (x^2+4)(x^2-1)=0 | | 3-2x=5-4x | | ln^2(x)=4x | | B=-3x+9y-5y+5x-4x+6y | | 12=4x+6 | | L=-9c+4b-8b+6c-3c+6b | | 9y-5=0 | | 10+2(2x-1)=16 | | (ln^2x)=4x | | (lnx^2)=4x | | 2x^2-60x=2x^2 | | W=-5c+3c-9+4 | | z+3(2-i)=5+i | | S=-5b-3b+6-7 | | x^2+x+2.5=0 | | D=-9c+6c-8c | | 64/x=4 | | A=-7y+6y | | 0.50x+0.25(30)=21.5 | | 50+(6x-2)=180 |